Different conformational responses of the β2-adrenergic receptor-Gs complex upon binding of the partial agonist salbutamol or the full agonist isoprenaline. Issue 9 (24th November 2020) - Yang, Fan; Ling, Shenglong; Zhou, Yingxin; Zhang, Yanan; Lv, Pei; Liu, Sanling; Fang, Wei; Sun, Wenjing; Hu, Liaoyuan A; Zhang, Longhua; Shi, Pan; Tian, Changlin
Abstract: G protein-coupled receptors (GPCRs) are responsible for most cytoplasmic signaling in response to extracellular ligands with different efficacy profiles. Various spectroscopic techniques have identified that agonists exhibiting varying efficacies can selectively stabilize a specific conformation of the receptor. However, the structural basis for activation of the GPCR-G protein complex by ligands with different efficacies is incompletely understood. To better understand the structural basis underlying the mechanisms by which ligands with varying efficacies differentially regulate the conformations of receptors and G proteins, we determined the structures of β2 AR-Gαs $β $ γ bound with partial agonist salbutamol or bound with full agonist isoprenaline using single-particle cryo-electron microscopy at resolutions of 3.26 Å and 3.80 Å, respectively. Structural comparisons between the β2 AR-Gs-salbutamol and β2 AR-Gs-isoprenaline complexes demonstrated that the decreased binding affinity and efficacy of salbutamol compared with those of isoprenaline might be attributed to weakened hydrogen bonding interactions, attenuated hydrophobic interactions in the orthosteric binding pocket and different conformational changes in the rotamer toggle switch in TM6. Moreover, the observed stronger interactions between the intracellular loop 2 or 3 (ICL2 or ICL3) of β2 AR and Gαs with binding of salbutamol versus isoprenaline might decrease phosphorylation in the salbutamol-activated β2 AR-Gs complex. From the observed structural differences between these complexes of β2 AR, a mechanism of β2 AR activation by partial and full agonists is proposed to provide structural insights into β2 AR desensitization.